The Influence of Firm Size, Profitability, and Audit Committee on Audit Delay: An Empirical Study of Public Companies in Indonesia - Listyarini, Rakhmawati; Umpusinga, Hasrun Afandi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The timeliness of financial reporting reflects the effectiveness of corporate governance and plays a vital role in maintaining investor confidence. Audit delay serves as a critical indicator of transparency and the quality of financial reporting among publicly listed companies. This study investigates the influence of firm size, profitability, and audit committee characteristics on audit delay in five leading manufacturing firms in Indonesia, namely PT Semen Indonesia Tbk, PT Indocement Tunggal Prakarsa Tbk, PT Indofood CBP Sukses Makmur Tbk, PT Unilever Indonesia Tbk, and PT Kalbe Farma Tbk, over the 2021–2023 period. Firm size is measured by the natural logarithm of total assets (Ln Assets), profitability is represented by Return on Assets (ROA), and the audit committee variable is determined by the number of its members. A multiple linear regression model is applied to test the effect of these variables on audit delay. The findings reveal that both firm size and profitability have a significantly negative relationship with audit delay, indicating that larger and more profitable firms tend to complete audits faster. The audit committee also exhibits a negative but moderate effect, emphasizing that effective governance contributes to shorter audit completion times. These outcomes align with agency theory and signaling theory, suggesting that timely reporting acts as a credibility signal and reduces agency costs. The study provides practical implications for corporate management, auditors, and regulatory bodies to enhance audit efficiency and strengthen investor confidence.